Frustration of freezing in a two dimensional hard-core fluid due to particle shape anisotropy - Huerta, A.; Tejeda, D.; Henderson, D.; Trokhymchuk, A. (Condensed Matter Physics, 2016)
The freezing mechanism suggested for a fluid composed of hard disks [Huerta et al., Phys. Rev. E, 2006, 74, 061106] is used here to probe the fluid-to-solid transition in a hard-dumbbell fluid composed of overlapping hard disks with a variable length between disk centers. Analyzing the trends in the shape of second maximum of the radial distribution function of the planar hard-dumbbell fluid it has been found that the type of transition could be sensitive to the length of hard-dumbbell molecules. From the NpT Monte Carlo simulations data we show that if a hard-dumbbell length does not exceed 15% the fluid-to-solid transition scenario follows the case of a hard-disk fluid, i.e., the isotropic hard-dumbbell fluid experiences freezing. However, for a hard-dumbbell length larger than 15% fluid-to-solid transition may change to continuous transition, i.e., such an isotropic hard-dumbbell fluid will avoid freezing. Механiзм замерзання, який був запропонований для плину жорстких дискiв [Huerta A. et al., Phys. Rev. E, 2006, 74, 061106], використовується тут для дослiдження фазового переходу плин-тверде тiло у системi, що складається з жорстких гантелеподiбних молекул, утворених двома жорсткими дисками зi змiнною вiдстанню мiж їх центрами. З аналiзу тенденцiй змiни форми другого максимуму радiальної функцiї розподiлу зроблено висновок, що тип фазового переходу плин-тверде тiло може бути чутливий до видовження гантелеподiбних молекул. На основi даних комп’ютерного експерименту Монте Карло при фiксованому тиску було знайдено, що коли видовження молекул не перевищує 15% дiаметра жорсткого диска, то фазовий перехiд плин-тверде тiло вiдбувається за тим же сценарiєм що i у системi жорстких дискiв, тобто плин гантелеподiбних молекул замерзає. У випадку, коли видовження молекул перевищує 15% дiаметра жорсткого диска, то є пiдстави стверджувати, що фазовий перехiд плин-тверде тiло проходить неперервно, тобто плин гантелеподiбних молекул у цьому випадку не замерзає.